Clinical results in the posterior pelvic injuries which are treated with percutaneous cannulated screw - Sen, Zafer; Kurtoğlu, Alper; Akkurt, Halil Ekrem; Yılmaz, Halim; Çöven, İlker (Progress in Nutrition, 2020)
Study Objectives: The sacrum is an important structure that provides approximately 70% of the body weight to be transmitted to the pelvic ring. Sacral fractures and associated sacroiliac joint injuries may occur with high-energy injuries in young people and low-energy trauma due to osteoporosis in elderly patients. Methods: 21 patients who underwent posterior pelvic ring injury between 2012 and 2020 at the Health Sciences University Konya Training and Research Hospital were studied. Percutaneous Sacroiliac Screwing (PSS) technique was used as the operation technique. Patients who had bilateral posterior ring injury and were operated on were studied. Results: There was no significant difference between demographical characteristics (age, gender) and the fracture type, and POS also (p>0.05). However, the weight of the patients in “fair” class was found significantly higher (p=0,026). Besides, the operation time was significantly lower in “excellent” and “good” POS classes (p=0.017). Conclusions: In the study performed by Chen et al., the exposure of scopy was found to be 22.1 shots 5. In our study, it was found to be 25.04 shots on average although the method was bilateral PSS. Although PSS has a learning curve, it is an easy-to-apply technique. Although bilateral PSS was used in our study, the duration was found to be 22 minutes. It can be concluded that PSS is a minimally invasive technique with a high learning curve and performing bilateral PSS through the same guide shortens the surgical time and reduces the exposure of scopy.